PERWALIAN ANAK DALAM TINJAUAN KOMPILASI HUKUM ISLAM - Harahap, Nurhotia (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2018)
The etymology of trusteeship (language), derived from the word guardian, and plural "awliya". This word comes from an Arabic word meaning "friend", "client", "relative", "protector". Terminology trust is the authority given to someone to carry out a legal act as a representative for the benefit and on behalf of a child who does not have both parents or parents are still alive but is not capable of doing legal actions.